Effectiveness of EGFR‐TKI rechallenge immediately after PD‐1 blockade failure. Issue 6 (31st January 2021) - Kaira, Kyoichi; Kobayashi, Kunihiko; Shiono, Ayako; Yamaguchi, Ou; Hashimoto, Kosuke; Mouri, Atsuto; Shinomiya, Shun; Miura, Yu; Imai, Hisao; Kagamu, Hiroshi
Abstract: Background: There is currently insufficient information available on effective therapies that can be administered to patients with non‐small cell cancer (NSCLC) who develop resistance to epidermal growth factor receptor‐tyrosine kinase inhibitors (EGFR‐TKIs). However, sequential treatment via programmed death‐1 (PD‐1) blockade followed by EGFR‐TKI rechallenge is suggested to improve the therapeutic efficacy in such patients. Methods: A total of 75 patients with advanced NSCLC harboring sensitive EGFR mutations treated with afatinib, erlotinib, or gefitinib after EGFR‐TKI treatment failure were retrospectively analyzed. Among them, 13 patients were treated with EGFR‐TKI rechallenge immediately after the failure of PD‐1 blockade therapy (experimental group) and the remaining 62 patients did not receive PD‐1 inhibitor therapy before EGFR‐TKI rechallenge (control group). Blood samples were collected at two time points; before the initiation of anti‐PD‐1 therapy and at EGFR‐TKI rechallenge. Results: The objective response rates of EGFR‐TKI rechallenge in the experimental and control groups were 46.1% and 16.1%, respectively, with a significant difference ( p = 0.026). In the experimental group, the median progression‐free survival (PFS) and overall survival (OS) after EGFR‐TKI rechallenge were 5.0 and 25.0 months, respectively, and no statistically significant difference in the percentage of lymphocytes before immune checkpoint inhibitor (ICI) therapy and EGFR‐TKIs was observed in patients with partial response (PR) and without PR after EGFR‐TKI rechallenge. In particular, the sequential treatment of PD‐1 blockade therapy followed by EGFR‐TKI rechallenge was consecutively repeated three times in two out of 13 patients in the experimental group, and EGFR‐TKI rechallenge consecutively for the third time yielded a PR without increased toxicities. Conclusions: EGFR‐TKI rechallenge immediately after PD‐1 blockade treatment was identified as an effective therapy for NSCLC patients with resistance to EGFR‐TKIs. Abstract : Repeated rechallenge of EGFR‐TKI EGFR‐TKI rechallenge immediately after PD‐1 blockade treatment may be effective for patients with resistance to EGFR‐TKIs. The results of our study provide a new strategy in sequencing treatment of lung cancer patients with EGFR mutation.